2010
DOI: 10.1007/s12031-010-9343-z
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Inducible Factor-1α (HIF-1α) and Some HIF-1 Target Genes are Elevated in Experimental Glaucoma

Abstract: Low levels of hypoxia have been suggested to be a mechanism of retinal damage in glaucoma. To test the hypothesis that the activation of the hypoxia-responsive transcription factor hypoxia inducible factor-1α (HIF-1α) is involved in the pathophysiology of glaucoma, we used a rat model of glaucoma to study (1) HIF-1α retinal protein levels by immunoblot analysis, (2) cellular localization of HIF-1α in the retina by immunohistochemistry, and (3) expression of retinal HIF-1 gene targets by quantitative real-time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 51 publications
(69 reference statements)
4
34
1
Order By: Relevance
“…HIF-1α plays a role in several retinal disorders (16,17). Nevertheless, our results do not substantiate a role for HIF-1α after hypoxia supported by several lines of evidence: (i) lack of HIF-1α stabilization, (ii) signaling events that trigger HIF-1α activation were not activated in choroid and even repressed in retina (10)(11)(12)(13).…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…HIF-1α plays a role in several retinal disorders (16,17). Nevertheless, our results do not substantiate a role for HIF-1α after hypoxia supported by several lines of evidence: (i) lack of HIF-1α stabilization, (ii) signaling events that trigger HIF-1α activation were not activated in choroid and even repressed in retina (10)(11)(12)(13).…”
Section: Discussioncontrasting
confidence: 85%
“…HIF-1α, which plays a major role during acute episodes of hypoxia (14) and its canonical target vascular endothelial growth factor alpha (VEGFA), involved in angiogenesis and vascular remodeling, exert neuroprotection during cerebral hypoxia-ischemia (8,15). Both HIF-1α and VEGF-α levels are altered in a number of retinal disorders, such as hypoxia/ischemia and retinopathy of prematurity and experimental evidence supports its role in promoting pathological angiogenesis (16,17). Intriguingly, at present it is unclear if a pathological state is favored by HIF-1α itself or by one of its target genes, like VEGFA.…”
mentioning
confidence: 99%
“…The inflammatory mediators TNF-a, IL-1b, and VEGF have been shown to decrease efficacy of the BRB. 45 VEGF is up-regulated during hypoxia 18 and enhances the adhesion of leukocytes to vascular walls and increases intercellular adhesion molecule-1 expression in the brain and retina, eliciting inflammation. 44 In addition, overexposure of VEGF in neural tissue has been shown to increase majorhistocompatibility complex class I and II, consequently initiating an inflammatory immune response and thereby a disruption of the BBB.…”
Section: Impairment Of the Blood--retinal Barrier Causes Vascularmentioning
confidence: 99%
“…75 Moreover, increased levels of NO occur in response to up-regulation of the transcriptional hypoxia-inducible-factor-1alpha (HIF-a), which is induced in ischemia-associated hypoxia in the retina and ONH. 18,79 Several other inflammatory molecules such as vascular endothelial growth factor (VEGF), tumor necrosis factor alpha (TNF-a), interleukins (IL), C-reactive protein (CRP) and serum amyloid A (SAA) have been shown to be up-regulated in glaucoma. 41,49,78,80,81,85 We aim to summarize the current evidence on the possible involvement of inflammatory responses in the pathogenesis of glaucoma (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…In normoxic conditions, HIF-alpha is bound to von Hippel-Lindau protein and is damaged by ubiquitination and proteosomal degradation. Specifically, recent results have shown that the HIF pathway can be used as a therapeutic target, although there is still a long way to go from bench to clinic [3][4][5].…”
Section: Introductionmentioning
confidence: 99%